Characteristics, Risk Factors And Outcome Of Early-Onset Delirium In Elderly Patients With First Ever Acute Ischemic Stroke - A Prospective Observational Cohort Study - Kotfis K (Dove Medical Press, 2019)
Katarzyna Kotfis,1 Marta Bott-Olejnik,2 Aleksandra Szylińska,3 Mariusz Listewnik,4 Iwona Rotter3 1Department of Anesthesiology, Intensive Therapy and Acute Intoxications, Pomeranian Medical University, Szczecin 70-204, Poland; 2Neurology Department of a Regional Specialist Hospital in Gryfice, Gryfice 72-300, Poland; 3Department of Medical Rehabilitation and Clinical Physiotherapy, Pomeranian Medical University, Szczecin 70-204, Poland; 4Department of Cardiac Surgery, Pomeranian Medical University, Szczecin 70-204, PolandCorrespondence: Katarzyna KotfisDepartment of Anesthesiology, Intensive Therapy and Acute Intoxications, Pomeranian Medical University, Szczecin, al, Powstańców Wielkopolskich 72, Szczecin 70-111, PolandTel/fax +48 91 466 1144Email katarzyna.kotfis@pum.edu.plIntroduction: Post-stroke delirium is a common clinical problem, occurring in 10% to 48% of patients. It has been associated with longer hospitalization times, increased mortality and worse functional outcome. In early phase of stroke, it may be regarded as particularly difficult to differentiate from other neurological symptoms. For practical purposes, there is a need to identify simple pre-operative laboratory parameters that may aid delirium diagnosis early after stroke. Our aim was to identify the incidence of early-onset (first 24 hrs) post-stroke delirium, its risk factors and outcomes (complications and mortality) in patients with first-ever acute ischemic stroke (AIS).Material and methods: A retrospective analysis of a prospective observational study (NCT03944694) was performed. Patients were screened for delirium using CAM-ICU method. Clinical and laboratory data were collected, including baseline inflammatory parameters.Results: Final analysis included 760 patients, 121 (15.9%) developed delirium. Patients with delirium were older (75.9±13.5 years, p<0.001). Most common complications in the delirium group were pulmonary (57.8% vs 21.4%, p<0.001), cardiac (38.8% vs 13.6%, p<0.001) and renal (13.2% vs 7.5%, p=0.038). Neutrophil-to-lymphocyte ratio (NLR) (6.71±9.65 vs 4.55±5.51, p<0.001), C-reactive protein level (32.59±65.94 vs 15.70±38.56, p<0.001) and troponin T level (72.59±180.15 vs 26.85±77.62, p<0.001) were higher in delirious patients and platelet-to white blood cell count ratio (PWR) (23.42±9.51 vs 27.13±10.58, p<0.001) was lower. Multivariable logistic regression showed that atrial fibrillation (OR 1.651, p=0.049), higher Rankin score on admission (OR 1.689, p<0.001), hemianopia (OR 2.422, p=0.003) and PWR <20.22 (OR 2.197, p=0.002) were independently associated with delirium. Kaplan–Meier curves indicated that mortality increased for patients with delirium at 3 months (p<0.001) and 1 year (p<0.001) after AIS.Conclusion: Atrial fibrillation, higher Rankin score, hemianopia and lower PWR were independently associated with early onset delirium in patients with first ever AIS. This confirms that deprivation of senses and early generalized inflammatory response are critical for delirium development.Keywords: delirium, first-ever stroke, PWR, CRP, NIHSS, CAM-ICU, acute brain dysfunction